Radiation shielding, structural, physical, and optical properties for a series of borosilicate glass - Mhareb, M.H.A.; Alajerami, Y.S.M.; Sayyed, M.I.; Dwaikat, Nidal; Alqahtani, Muna; Alshahri, Fatimh; Saleh, Noha; Alonizan, N.; Ghrib, Taher; Al-Dhafar, Sarah Ibrahim (Journal of non-crystalline solids, 2020)
The current study explores the effect of BaO content on the shielding, optical, structural, and physical features of 10TiO2–10SiO2-(80-x)B2O3-xBaO (10 ≤ x ≤ 30) glass samples for their ability to be used as radiation shielding substances. X-ray diffraction spectra affirmed the amorphous state for all prepared samples. A series of physical parameters confirm the stability of the prepared glasses. The optical properties confirm the forming of non-bridging oxygens and these results are in line with the physical and structural properties and FTIR results. Regarding the shielding properties, the mass attenuation coefficient was measured experimentally and compared with the compatible values obtained from the XCOM program. Furthermore, other photon shielding properties, such as radiation protection efficiency, mean free path, exposure buildup factor, and energy absorption buildup factor, were calculated within the energy range of 15 keV-15 MeV. It was determined that this glass composition is suitable for photon radiation shielding applications.